(untitled) (Research, Society and Development, 2024)
Objective: to identify the clinical-epidemiological profile of patients reported with bone tuberculosis (TBO) in Rio Grande do Sul from 2010 to 2021. Methods: the 575 reported cases of TBO were analyzed in an observational way, of a quantitative nature, of an ecological type and of descriptive character, carried out with data from the Notifiable Diseases Information System (SINAN). Results: BOD was more prevalent in men (65.4%) aged between 40 and 59 years (37.9%) and with low education, with a significant portion of them being smokers and/or alcohol drinkers. Co-infection with HIV proved to be relevant in this context, affecting 17.5% of the sample. Furthermore, only 117 of the 497 municipalities reported the disease. Conclusion: it is essential to monitor the progression of tuberculosis across the country, improve health surveillance and promote preventive and educational measures for the general population.